Potret Kontestasi Politik Lokal: Analisis Kegagalan Kolaborasi Caleg Tandem dalam Pemilu Legislatif Kabupaten Badung Tahun 2024 - Maharani, Pande Putu Regina; Apriani, Kadek Dwita (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This study aims to determine the failure factors of the collaboration of tandem legislative candidates at the Regency level, Badung Regency, with legislative candidates at the Provincial level, Bali Province (Badung Electoral District), who use this strategy as an opportunity to gain votes. Research methods: The research methodology used is qualitative with research data collection through interviews and documentation with target informants. Results and discussion: This finding explains the social phenomenon of the failure of the local tandem legislative candidate Ni Komang Tri Ani who paired herself with her tandem partner, I Bagus Alit Sucipta, so that she won an absolute victory with newcomer status in the 2019 Election. As if defending her seat, Tri Ani returned to the political contest in the 2024 Election but failed to secure her seat when she changed her tandem partner to Wayan Bawa. One strategy that has attracted quite a lot of attention is the replacement of political actors as tandem partners. Implication: With the political dynamics of the tandem legislative candidate pair and the failure of Ni Komang Tri Ani to secure her seat again, the internal factors between candidates within the political party became a factor in Ni Komang Tri Ani not maintaining the collaboration of the previous tandem pair, thus changing the political actors in the next election.